The Effects of GABAergic System under Cerebral Ischemia: Spotlight on Cognitive Function - Juan Li; Luting Chen; Feng Guo; Xiaohua Han (Neural Plasticity)
In this review, we present evidence about the changes of the GABAergic system on the hippocampus under the ischemic environment, which may be an underlying mechanism to the ischemia-induced cognitive deficit. GABAergic system, in contrast to the glutamatergic system, is considered to play an inhibitory effect on the central nervous system over the past several decades. It has received widespread attention in the area of schizophrenia and epilepsy. The GABAergic system has a significant effect in promoting neural development and formation of local neural circuits of the brain, which is the structural basis of cognitive function. There have been a number of reviews describing changes in the GABAergic system in cerebral ischemia in recent years. However, no study has investigated the changes in the system in the hippocampus during cerebral ischemic injury, which results in cognitive impairment, particularly at the chronic ischemic stage and the late phase of ischemia. We present a review of the changes of the GABAergic system in the hippocampus under ischemia, including GABA interneurons, extracellular GABA neurotransmitter, and GABA receptors. Several studies are also listed correlating amelioration of cognitive impairment by regulating the GABAergic system in the hippocampus damaged under ischemia. Furthermore, exogenous cell transplantation, which improves cognition by modulating the GABAergic system, will also be described in this review to bring new insight and strategy on solving cognitive deficits caused by cerebral ischemia.